Safety and feasibility of tracheostomy and gastrostomy home replacement: a five-year experience from a palliative care center - Burlo, Francesca; Bortolin, Irene; Grasso, Domenico Leonardo; Oveglia, Anna; Barbi, Egidio; De Zen, Lucia; Taucar, Valentina; Peri, Francesca (Frontiers in Pediatrics, 2025)
BackgroundChildren with medical complexities needing palliative care often rely on tracheostomy and gastrostomy tubes. As home-based care gains priority to improve well-being and reduce hospitalizations, this study evaluates the safety and feasibility of home replacement of these devices.MethodsThe study was a cross-sectional observational study of pediatric tracheostomy and/or gastrostomy patients followed at home by the Friuli-Venezia Giulia Regional Pediatric Palliative Care Centre at the Institute for Maternal and Child Health IRCCS “Burlo Garofolo”, Trieste. Data were consecutively collected between March 2020 and October 2024 by reviewing patients' medical records. A general satisfaction survey was additionally sent to caregivers.ResultsThe study sample included 14 children with a median age of 11 years (range 2–18 years). Among them, 3 (21%) had a tracheostomy, 7 (50%) had a gastrostomy and 4 (29%) had both devices. From 2020 to the present, 77 tracheostomy tube changes and 82 gastrostomy button changes were performed. No complications occurred. Families expressed high satisfaction with home device replacements, with nearly all preferring them over hospital-based changes.ConclusionThis study shows the safety and feasibility of home tracheostomy and gastrostomy replacement, highlighting the strong preference of patients' families for these procedures. By ensuring a secure approach, they help preserve the quality of life for both patients and their families.